Giant sacrococcygeal teratoma in neonate: A case report and review of literature - Rajkumar Motiram Meshram; R Nikila; Nilesh Nagdive (Indian Journal of Medical and Paediatric Oncology)
Sacrococcygeal teratoma is considered the most common tumor in the neonatal period with a female-to-male ratio of 3–4:1. They are believed to arise early in gestation from the totipotential cells of Hensen's node and the derived ectoderm, mesoderm, and endoderm. A 2.25 kg cesarean-delivered male, term neonate presented with large nonpulsatile, globular erythematous mass with lobulated surface and variable consistency. Magnetic resonance imaging of the lumbosacral spine showed multilocular cystic and solid lesion with foci of calcification and subtle communication with spinal canal. Histopathological examination showed mature endodermal, ectodermal, and mesenchymal elements such as cartilage, glial tissues, keratin cyst, and glandular elements with focus of primary neuroepithelial and pancreatic elements. Entire tumor was excised. The baby expired secondary to wound infection. Early diagnosis by improving antenatal care with timely surgical intervention and good nursing care improves the outcome.